2006
DOI: 10.1007/s00134-006-0367-3
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy prevents coagulation disorders in an experimental model of multiple organ failure syndrome

Abstract: The hypercoagulability induced by zymosan could be responsible for organ failure and death. Our data demonstrate that HBO therapy significantly prevents the alteration in the coagulation cascade and arterial blood gas in an experimental model of MOFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Our results confirm the point of view, that early HBOT application in MI patients, results in faster eradication of misbalanced oxygen myocardial need and delivery, which contributes to MI area reduction, scar healing with "softer" collagen tissue, aneurysm prevention [28,35]. It has been demonstrated in an experimental condition that the influence of hyperbaric oxygenation prevents the development of hypercoagulation syndrome [36], HBOT application immediately after coronary occlusion reduces myocardial necrosis and acute mortality in rats [37]. The beneficial effects of HBOT in treating ischemia-related wounds may be mediated by stimulating angiogenesis [27].…”
Section: Discussionsupporting
confidence: 87%
“…Our results confirm the point of view, that early HBOT application in MI patients, results in faster eradication of misbalanced oxygen myocardial need and delivery, which contributes to MI area reduction, scar healing with "softer" collagen tissue, aneurysm prevention [28,35]. It has been demonstrated in an experimental condition that the influence of hyperbaric oxygenation prevents the development of hypercoagulation syndrome [36], HBOT application immediately after coronary occlusion reduces myocardial necrosis and acute mortality in rats [37]. The beneficial effects of HBOT in treating ischemia-related wounds may be mediated by stimulating angiogenesis [27].…”
Section: Discussionsupporting
confidence: 87%
“…A correlation between a portal hypertensive effect and a decrease in systemic arterial pressure in intact animals was indeed demonstrated by Shibamoto et al [38] and Kaufman and Levasseur [15]. These observations support the hypothesis that the liver hemodynamic changes could contribute, partly at least, to the systemic pressure reduction observed in the zymosaninduced multiple-organ failure syndrome [13].…”
Section: Discussionmentioning
confidence: 63%
“…As the uptaking of gluconeogenic substrates from the circulation seems to be also reduced [18], the role of the liver in the maintenance of glycemia in the fasted condition could be also compromised. These metabolic consequences of the zymosanvascular changes along with the possible consequences for the macrohemodynamics of the intact animals may contribute to the development of the zymosan-induced multiple organ failure syndrome [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imperatore and colleagues have previously demonstrated that intermittent hyperbaric oxygen (HBO) therapy is effective in attenuating this process in a zymosan-induced MOFS model in rats. They have now published a further study concentrating on the effects of HBO on the coagulation cascade [ 3 ]. The zymosan insult produced a marked coagulopathy, MOFS and a 50% mortality at 72 hours in the control group.…”
Section: Confused By Oxygen?mentioning
confidence: 99%